Microarray-based analysis and clinical validation identify ubiquitin-conjugating enzyme E2E1 (UBE2E1) as a prognostic factor in acute myeloid leukemia. Issue 1 (December 2016) - Luo, Hongmei; Qin, Yu; Reu, Frederic; Ye, Sujuan; Dai, Yang; Huang, Jingcao; Wang, Fangfang; Zhang, Dan; Pan, Ling; Zhu, Huanling; Wu, Yu; Niu, Ting; et al.
Abstract Background Previous research suggested that single gene expression might be correlated with acute myeloid leukemia (AML) survival. Therefore, we conducted a systematical analysis for AML prognostic gene expressions. Methods We performed a microarray-based analysis for correlations between gene expression and adult AML overall survival (OS) using datasets GSE12417 and GSE8970. Positive findings were validated in an independent cohort of 50 newly diagnosed, non-acute promyelocytic leukemia (APL) AML patients by quantitative RT-PCR and survival analysis. Results Microarray-based analysis suggested that expression of eight genes was each associated with 1-year and 3-year AML OS in both GSE12417 and GSE8970 datasets (p  < 0.05). Next, we validated our findings in an independent cohort of AML samples collected in our hospital. We found that ubiquitin-conjugating enzyme E2E1 (UBE2E1 ) expression was adversely correlated with AML survival (p  = 0.04). Multivariable analysis showed thatUBE2E1 high patients had a significant shorter OS and shorter progression-free survival after adjusting other known prognostic factors (p  = 0.03). At last, we found thatUBE2E1 expression was negatively correlated with patients' response to induction chemotherapy (p  < 0.05). Conclusions In summary, we demonstrated thatUBE2E1 expression was a novel prognostic factor in adult, non-APL AML patients.